Հոգեկան հիվանդություն և ստեղծագործական ակտիվություն - Սարգսյան, Սյուզան (Զանգակ հրատ.)
В статье рассматриваются вопросы, связанные с психологией творчества, в частности, как влияет патологическое изменение психики на творческую деятельность. Болезнь может расширить рамки психологического опыта художника, позволить ему острее воспринимать мир. Иногда душевные болезни обладают способностью внезапно вскрывать творческий потенциал человека. The article deals with issues related to the psychology of creativity, in particular, how pathological changes in the human psychology affect the visual activity. Disease can expand the scope of the artist՛s psychological experience, which allows him to perceive the world more acutely. Sometimes mental illnesses have the ability of disclosing the creative potential of a person.
Keywords: Հոգեբանություն